Biogeography and taxonomy of Ophiuroidea (Echinodermata) from the Îles Saint-Paul and Amsterdam in the southern Indian Ocean - O’hara, Timothy D.; Thuy, Ben (Zootaxa, 2022)
The ophiuroid fauna of the Île Amsterdam and Île Saint-Paul territories (SPA) is reviewed. Four new species are described: Ophiolebes felli, Ophiolebes paulensis, Ophiocomina arnaudi and Amphiura remota. Recent phylogenetic results required a partial reorganisation of Ophiacanthidae and Amphiuridae genera, including the transfer of some Ophiacantha and Ophiomitrella species to a new genus Ophiosabine (O. rosea, O. anomala, O. aristata, O. cuspidata, O. densispina, O. nodosa, O. notata, O. parcita, O. pentactis, O. vivipara, O. wolfarntzi) and existing genera Ophiosemnotes (O. conferta, O. ingrata, O. corynephora, O. clavigera, O. hamata) and Ophiolebes (O. yaldwyni), Ophiacantha spectabilis to Ophiotreta in the Ophiotomidae, and some Amphioplus species to Amphiura (A, acutus, A. ctenacantha, A. cipus). The combination Ophiophycis nixastrum is restored. The SPA endemic species Ophiocten lymani and Amphiura brevispina, and the southern Australian/New Zealand species Ophiactis cuspidata and Ophiocten australis, are recognised as valid species. The North Atlantic species Ophiura ljungmani, Ophiacantha veterna, Ophiosabine cuspidata, Ophiolimna bairdi and Ophiactis nidarosiensis are recorded from the southern Indian Ocean. Shallow water specimens of Ophiura ljungmani from the Western Atlantic are re-identified as O. fallax and O. acervata. The monotypic Ophiothauma heptactis from northern Australia is synonymised with Ophiocomella sexradia and thus the genus Ophiothauma with Ophiocomella. The biogeography of the ophiuroid fauna reflects the position of the islands near the eastward-flowing currents of the South Indian Ocean gyre. The closest affinities are with faunas in the SW Indian Ocean and SE Atlantic Ocean. Despite its proximity, no species are shared with the Kerguelen Plateau to the south. The large temperature gradient across the subtropical front between Île Saint-Paul and Kerguelen appears to be a distribution limit for littoral and upper bathyal invertebrates.